White and Red Sorghum as Primary Carbohydrate Sources in Extruded Diets of Felines - von Schaumburg, Patrick; He, Fei; Rodriguez-Zas, Sandra L.; Southey, Bruce R.; Parsons, C. M.; de Godoy, Maria R. C. (Frontiers in Veterinary Science, 2021)
The research objectives were to evaluate the effect of dietary supplementation of white (WSH) and red (RSH) sorghum grains on gastrointestinal health of felines through the determination of apparent total tract macronutrient digestibility (ATTD), fecal characteristics, fermentative end-products, and microbiota, compared with a traditional corn-based diet. We hypothesize that inclusion of RSH and WSH, respectively, would be well-accepted by cats, and the RSH and WSH diets would be comparable to corn when added as the main carbohydrate source in extruded diets. Three diets containing 30% corn, 30% WSH, or 30% RSH were formulated to meet or exceed the AAFCO (2018) nutrient profiles for cats during growth. Nine male cats (0.8 ± 0.00 yr) were randomly assigned to one of the three dietary treatments using a triplicated 3 × 3 Latin square design. Experimental periods consisted of 14 d (10 d of diet adaption and 4 d of total and fresh fecal collections). The ATTD of dry matter (DM) did not differ amongst treatments, organic matter was greatest (P < 0.05) for both sorghum diets (86.4%) and lowest for the corn diet (84.2%), crude protein was comparable among diets ranging from 84.5 to 86.6%, acid hydrolyzed fat was high among diets varying between 91.4 and 92.8%, and total dietary fiber was greatest (P < 0.05) for the WSH diet (56.0%) with the corn diet being lowest (44.7%). Digestible energy was greatest (P < 0.05) for the WSH diet (4.66 kcal/g) and lowest for the corn diet (4.54 kcal/g), with the RSH diet being intermediate (4.64; P > 0.05). Fecal pH (6.3–6.5) and most fecal metabolites did not differ among diets except for phenol/indole concentrations that were significantly lower (P < 0.05) in cats fed the RSH diet (1.5 μmole/g DM) than for cats fed the corn diet (2.1 μmole/g DM). Bacteroidetes, Firmicutes, Fusobacteria, and Proteobacteria were the major phyla observed in the microbiota of feces of cats fed the three experimental diets, with no differences seen amongst all treatments. Data indicate that dietary supplementation of these varieties of WSH and RSH as carbohydrate sources were well-tolerated by the cat.